Renal Rehabilitation-Its Theory and Clinical Application to Patients Undergoing Daily Dialysis Therapy - Ryota Matsuzawa; Daisuke Kakita (MDPI AG, 2022)
An aging population and the prevalence of lifestyle-related ailments have led to a worldwide increase in the rate of chronic kidney disease requiring renal replacement therapy. The mean age of people requiring dialysis has been rising, and Japanese patients are aging more rapidly than those in the United States and Europe. Compared to people with normal kidney function, those undergoing hemodialysis are at increased risk of sarcopenia or frailty and serious health problems that limit access to kidney transplantation and lead to adverse health outcomes such as functional dependence, hospitalization, and death in patients on dialysis treatment. The Japanese Society of Renal Rehabilitation, established in 2011, published a clinical practice guideline for renal rehabilitation in 2019. Although the concept has become widely known among kidney health providers in recent years, efforts have still not focused on routine clinical care for patients with chronic kidney disease. In this review, the theory and clinical application of renal rehabilitation for patients undergoing daily hemodialysis were investigated.